Acesso à justica : Projeto Florença e Banco Mundial - Porto, Júlia Pinto Ferreira (2009)
This work deals with concepts of access to justice considered in two models: the Movement for Access to Justice Project expressed in Florence in the seventies, and recommendations from the World Bank to reform the judicial sector in Latin America and Caribbean , especially as expressed in Document 319S. Thus, the research finding, tracing profiles on the appropriate theoretical concepts of state and right of each model were compared the proposed access at the discretion of the space to the category of poverty in each. For this, the concepts covered in the proposals of the Welfare State Project Florence, and a state inserted in the context of globalization to the recommendations of the Bank. Thus, demonstrates that the type of access set out in Florence Project through its three waves addresses the concern about the effectiveness of social rights, and that the recommendations of the Bank are included in a speech proposing the opening of markets and a Judicial least. With that, search is the analysis of access to justice democracy, able to incorporate spaces for nonprivileged, without, however, play model of inequality.